Peningkatan Pemahaman Hukum Masyarakat dalam Upaya Pencegahan Perjudian Online di Desa Girisekar Kecamatan Panggang Kabupaten Gunungkidul Yogyakarta - Fakultas Hukum Universitas Negeri Surabaya; Apriliani Kusumawati; Pudji Astuti; Gelar Ali Ahmad; Vita Mahardhika; Rendy Airlangga; Nur Hafizal Hasanah (Jurnal Darma Loka, 2025)
Although online gambling is often seen as a common urban issue, it has increasingly spread to rural areas with the expansion of digital infrastructure. Girisekar Village in Panggang District, Gunungkidul Regency, is one such area at risk. This highlights the urgent need for comprehensive prevention efforts to reduce online gambling vulnerability. These efforts involved a legal counseling workshop aimed at enhancing public understanding of the law to prevent online gambling. The workshop covered topics such as: (1) Overview of Online Gambling; (2) Trends in Indonesian Online Gambling Cases; (3) Negative Effects of Online Gambling; (4) Legal Penalties for Online Gambling; and (5) Family and Community Strategies for Prevention. The content was delivered systematically, supported by visual aids. Pre-test and post-test results showed a significant improvement in the community’s legal awareness regarding online gambling. Additionally, this activity fostered increased community participation in prevention efforts, serving as valuable social capital to create an environment free from online gambling.